2020
DOI: 10.1155/2020/4598476
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia Impairs NK Cell Cytotoxicity through SHP-1-Mediated Attenuation of STAT3 and ERK Signaling Pathways

Abstract: Natural killer (NK) cells are innate immune effectors with potent antitumor activity. However, tumor cells can create an immunosuppressive microenvironment to escape immune surveillance. Although accumulating evidence indicates that microenvironmental hypoxia plays an important role in favoring tumor development and immune evasion, it remains unclear by what means hypoxia directly impairs NK cell antitumor activity. In this study, we confirmed that hypoxic NK cells showed significantly lower cytotoxicity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…HIF1α also is an important metabolic regulator under certain normoxic conditions and plays an crucial role in supporting glycolysis and effector function in CD8+ cytotoxic T cells [ 55 ]. However, HIF1α is not a key regulator of NK cell metabolism and the data suggests that HIF1α expression in NK cells can have pro-tumour effects [ 65 , 66 ]. HIF1α-deficient NK cells have normal metabolic and effector function responses following IL2+IL12 cytokine stimulation under normoxic conditions, suggesting HIF1α is dispensable for normal cytokine-induced NK cell responses [ 8 ].…”
Section: Metabolic Signalling As Potential Therapeutic Targets In Nk mentioning
confidence: 99%
“…HIF1α also is an important metabolic regulator under certain normoxic conditions and plays an crucial role in supporting glycolysis and effector function in CD8+ cytotoxic T cells [ 55 ]. However, HIF1α is not a key regulator of NK cell metabolism and the data suggests that HIF1α expression in NK cells can have pro-tumour effects [ 65 , 66 ]. HIF1α-deficient NK cells have normal metabolic and effector function responses following IL2+IL12 cytokine stimulation under normoxic conditions, suggesting HIF1α is dispensable for normal cytokine-induced NK cell responses [ 8 ].…”
Section: Metabolic Signalling As Potential Therapeutic Targets In Nk mentioning
confidence: 99%
“…Expression of NCRs is reduced relative to healthy controls in an effect reliant on NK and blast cell contact [ 85 ]. NKG2D downregulation occurs secondary to chronic exposure to hypoxia, cell surface and soluble NKG2D ligands and via blast and stroma derived TGF-β [ 86 , 87 , 88 ]. NKG2A expression is often increased, at least partially driven by blast cell production of IL-10, while IFN-γ induces expression of the ligand for NKG2A (HLA-E), on blast cells [ 89 , 90 ].…”
Section: Natural Killer Cells and Amlmentioning
confidence: 99%
“…MDSC populations upregulate CD155 in response to ROS, impairing traditional NK cell but not adaptive NK cell function reflecting differing TIGIT expression [ 106 ]. Finally, hypoxia has been associated with varied inhibitory NK cell effects including reduced activating receptor expression and impaired production of IFN-γ [ 88 , 107 ]. The transcription factor HIF1α is a clinically relevant mediator of hypoxia related NK cell inhibition in cancer [ 108 ].…”
Section: Natural Killer Cells and Amlmentioning
confidence: 99%
“…Hypoxic NK cells also exhibited lower cytotoxicity against FO-1 melanoma cells due to impaired degranulation [ 105 ]. Recent investigations have revealed that hypoxia in NK cells induces the activity of protein tyrosine phosphatase SHP-1 (Src homology region 2 domain-containing phosphatase-1), which attentuates STAT3 and ERK signalling leading to an impairment of NK cell function [ 106 ]. Moreover, tumor cells have evolved to use hypoxic stress to their advantage through HIF activation [ 107 , 108 ], resulting in immune suppression and tolerance to immune surveillance by promoting MDSC accumulation, inhibiting DC maturation, and recruiting T regs , which ultimately impair NK cell function [ 104 , 108 , 109 ].…”
Section: The Evidence: Understanding the Mechanisms Of Postoperative Natural Killer Cell Suppressionmentioning
confidence: 99%